Światłość Bożego mieszkania według pism qumrańskich w kontekście tradycji biblijnej i apokryficznej - Targoński, Mateusz (Verbum Vitae, 2016)
The article explores the ways in which the writings of the Qumran community use the metaphor of light to describe God’s dwelling. The first part outlines the background contained in the Hebrew Bible, which permits an understanding of the theological foundations of Judaism in the Second Temple period. The second part considers the two important non-canonical texts of greatest importance to the Qumran community, namely First Book of Enoch and Book of Jubilees. The last part analyses the four Qumran sectarian works which employ the “light of God’s dwelling” imagery: Songs of Sabbath Sacrifice, Blessings and Curses, Songs of the Maskil and Works of God. Also examined are examples of the broader eschatological use of light in other texts of the community. Light, when used to describe God’s dwelling, emphasises the perfection of a heavenly palace and the unapproachability of the Creator by the man during his earthly lifetime.